2007
DOI: 10.1007/s11292-007-9048-7
|View full text |Cite
|
Sign up to set email alerts
|

Drunk and dangerous: a randomised controlled trial of alcohol brief intervention for violent offenders

Abstract: To assess the effectiveness of an alcohol brief intervention administered to violent offenders in a judicial (Magistrates' court) setting, a randomised controlled trial was conducted. Participants (n=269) were men aged 16-35 years, who resided within a 30-mile radius of Cardiff, UK, and who had been sentenced for a violent offence committed whilst intoxicated with alcohol. Recruitment occurred on-site. Participants were randomly allocated to receive an alcohol brief intervention (n= 135) or to a control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 25 publications
0
42
1
Order By: Relevance
“…This is primarily because of the issues related to when and how you measure alcohol consumption when someone is incarcerated for a long period of time. The studies that have been carried out in the UK in other criminal justice areas have shown no effect on reduced drinking (Watt et al, 2008;Newbury-Birch et al, 2014). However, effects relating to fewer injuries have been shown and there is some promising work with young people in the USA (Stein et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is primarily because of the issues related to when and how you measure alcohol consumption when someone is incarcerated for a long period of time. The studies that have been carried out in the UK in other criminal justice areas have shown no effect on reduced drinking (Watt et al, 2008;Newbury-Birch et al, 2014). However, effects relating to fewer injuries have been shown and there is some promising work with young people in the USA (Stein et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…Prison -remand and sentenced (100% male) (n ¼ 216) (Watt and Shepherd, 2005;Watt et al, 2008). It is important to note though, that eligibility to be screened was that the participant had been sentenced for a violent offence committed whilst intoxicated with alcohol.…”
Section: Magistrates' Courtmentioning
confidence: 99%
See 1 more Smart Citation
“…Although very limited in number and methodological quality, there is some evidence on brief intervention for heavy drinkings such as psychiatric outpatient setting, [45] community-based counselling centres, sexual health clinics, and antenatal care and postpartum care settings [46][47][48][49]. However, none of the studies reported a superior benefit for brief intervention as compared to routine care [50,51].…”
Section: Alcohol Brief Interventions In Miscellaneous Settingsmentioning
confidence: 99%
“…10, for social sciences generally), no consensus on standards similar to that seen in the health sciences has been reached. Recently, several reports of RCTs in the Journal of Experimental Criminology have explicitly and voluntarily adhered to CONSORT standards (e.g., Sherman et al 2005;Watt et al 2008;Barnes et al 2010). Perry and Johnson (2008) provide empirical evidence that criminological trial reports only partially adhere to CONSORT.…”
mentioning
confidence: 99%